The Effectiveness of Using Google Classroom in Improving the Ability to Write Historical Story Texts - Hayani, Rizka (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2018)
This study aims to describe the effectiveness of Google Classroom in improving the skills of writing historical narrative texts for grade XII IIS-1 students of SMAN 1 Terusan Nunyai. The type of this research is Classroom Action Research (CAR). The research design used is the Kemmis and Mc.Taggart model which consists of four components, namely: planning, action, observation, and reflection. The research location is in SMAN 1 Terusan Nunyai, Central Lampung. The research subjects were students of grade XII IIS 1, totally 30 students. The success criteria achieved by students in this study were seen from the changes for the better and the increase in learning acts and results in the practice of writing historical narrative texts. The results of the study show the following. First, the use of Google Classroom can improve the quality of the learning process for writing historical narrative texts. There is an increase in the process in aspects of the learning situation, student focus, and activity, making positive changes so that learning to write historical story texts is more interesting and fun. Second, learning to write Historical Story Texts with Google Classroom can improve the results of historical story writing skills. This can be figured out from the average score of writing historical narrative text skills in the first cycle is 73.7 while after being given an action in the second cycle the average score becomes 78.8. This shows an increase of 5.1. Overall, at the end of cycle II, all aspects and criteria for writing historical narrative texts experienced a significant increase.